The Merchant of Venice: the Activity of Patricians in the Late Middle Ages - Hocquet, Jean-Claude, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
For the first time, The Merchant of Venice looks at the place and role of the late medieval merchant nobility in the great international trade that took place in the world known at the time, from China and Asia to Flanders and England. These merchants who travelled the world were also shipowners, sailors and bankers. They used modern banking techniques and credit based on bills of exchange held no secrets for them. They traded spices, porcelain, cotton and silk, dyes and glassware for drapery, wool and metals. These merchants used part of their profit to embellish their city, which amazed foreign visitors, and were always on the lookout for the latest discoveries and inventions. Venice was at the height of its power at the time, but it was also on the eve of its weakening.